Scaffold-Mediated Developmental Effects on Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes Are Preserved After External Support Removal - Li, Jun; Lee, Jong-Kook; Miwa, Keiko; Kuramoto, Yuki; Masuyama, Kiyoshi; Yasutake, Hideki; Tomoyama, Satoki; Nakanishi, Hiroyuki; Sakata, Yasushi (Frontiers in Cell and Developmental Biology, 2021)
Human induced pluripotent stem cells (hiPSCs) have been utilized as a cell source for regenerative therapy and disease modeling. Owing to their ability of proliferating infinitely and differentiating into spontaneously beating cardiomyocytes, hiPS-derived cardiac tissue has been considered a promising candidate for understanding cardiac physiological development and pathological progression. The purity of hiPS-cardiomyocytes (CMs) has markedly improved with advancements in cell culture and differentiation. However, the morphological features and molecular properties of the relatively immature cells are still not clear, which has hampered their clinical application. Well-aligned cardiac tissue has been successfully obtained by culturing PSC-CMs on an anisotropic pattern, although its effects on PSC-CM maturation are still ambiguous. Hence, the aim of the present study was to investigate the extent to which topographic substrates actively influence hiPS-CMs. hiPS-CMs were seeded on randomized oriented fiber substrate (random), anisotropic aligned fiber substrate (align), and flat non-scaffold substrate (flat). After culturing for one week, the hiPS-CMs on the aligned patterns showed more mature-like properties, including elongated rod shape, shorter duration of action potential, accelerated conduction velocity, and elevated cardiac gene expression. Subsequently, to determine whether this development was irreversible or was altered after withdrawal of the structural support, the hiPS-CMs were harvested from the three different patterns and reseeded on the non-scaffold (flat) pattern. After culturing for one more week, the improvements in morphological and functional properties diminished, although hiPS-CMs pre-cultured on the aligned pattern retained the molecular features of development, which were even more significant as compared to that observed during the pre-culture stage. Our results suggested that the anisotropic fiber substrate can induce formation of geometrical mimic-oriented heart tissue in short time. Although the morphological and electrophysiological properties of hiPS-CMs obtained via facilitated maturation somehow rely on the existence of an exterior scaffold, the molecular developmental features were preserved even in the absence of the external support, which might persist throughout hiPS-CM development.